ANALYSIS OF OVERTIME WORK PRODUCTIVITY AND WAGE SUITABILITY IN THE WORKFORCE OF THE BANJARMASIN-MARTAPURA ROAD RECONSTRUCTION PROJECT SECTION II - Badarudin, Ahmad; Yuliana, Candra (CERUCUK, 2025)
In an effort to meet the deadline for the Banjarmasin – Martapura Road Reconstruction Project Section II, the implementing party often accelerates the schedule by implementing an overtime work system. To determine the labor productivity of the Banjarmasin – Martapura Road Reconstruction Project Section II, this study uses the partial productivity method. This method compares the time used per day as the input value with the amount of work produced each day as the output value.The results of the calculation obtained from the productivity analysis using a partial approach are obtained that the average productivity of normal working hours in paving work is 15,923 m3/hour and in road shoulder casting work is 1,877 m3/hour. The average productivity of overtime working hours for paving work was 16,285 m3/hour and for casting work was 2,190 m3/hour. From the results obtained, it is known that the productivity value of overtime working hours is greater than the productivity of normal working hours, this is due to obstacles that occur, namely the asphalt and concrete production process from AMP (Asphalt Mixing Plant) which is late because the engine that often breaks down is also because this road project is in the middle of a dense community so that the material process to the location often experiences delays. By implementing overtime working hours, the labor wage budget increased by 86.717%. However, the amount of overtime wages implemented by the Banjarmasin – Martapura Road Reconstruction Project Section II is not in accordance with the amount of wages according to the provisions of Government Regulation No. 35 of 2021. Keywords: Partial productivity, overtime work, overtime wages, labor